2018
DOI: 10.1002/ecs2.2440
|View full text |Cite
|
Sign up to set email alerts
|

Surviving in the city: higher apparent survival for urban birds but worse condition on noisy territories

Abstract: Anthropogenic landscapes and soundscapes impose strong selective pressures on a number of species, which can manifest in changes in vocalizations, foraging strategies, predator vigilance, and reproductive success. However, few studies have examined survival rates, a major component of fitness, across urban landscapes and soundscapes. White‐crowned sparrows (Zonotrichia leucophrys) persist in both urban and rural landscapes and change their behavior in response to the soundscape. We color‐banded adult white‐cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 62 publications
(104 reference statements)
2
15
0
Order By: Relevance
“…Increases in low frequency noise can have physiological effects on rodents by triggering stress responses (Du et al 2010) and altering organ tissue (Branco et al 2004), even if the frequency of the noise is below the range at which the rodents can likely hear (see below). A similar pattern of reduced body condition or changes in stress hormones in noisy areas has been found in multiple bird species as well, providing further evidence that elevated levels of ambient noise can induce negative, physiological effects (Kleist et al 2018, Phillips et al 2018. If these or similar direct, physiological effects occur in natural systems from noise levels and frequencies that pinyon mice can or cannot detect, it could result in an equal use ecological trap where individuals do not avoid habitat that is ultimately deleterious (Hale and Swearer 2016).…”
Section: Discussionsupporting
confidence: 62%
“…Increases in low frequency noise can have physiological effects on rodents by triggering stress responses (Du et al 2010) and altering organ tissue (Branco et al 2004), even if the frequency of the noise is below the range at which the rodents can likely hear (see below). A similar pattern of reduced body condition or changes in stress hormones in noisy areas has been found in multiple bird species as well, providing further evidence that elevated levels of ambient noise can induce negative, physiological effects (Kleist et al 2018, Phillips et al 2018. If these or similar direct, physiological effects occur in natural systems from noise levels and frequencies that pinyon mice can or cannot detect, it could result in an equal use ecological trap where individuals do not avoid habitat that is ultimately deleterious (Hale and Swearer 2016).…”
Section: Discussionsupporting
confidence: 62%
“…These levels of noise have been shown to affect the body condition (Phillips et al . ), behavior (Klett‐Mingo et al . ), and fitness (Schroeder et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although NPS lands are among the quietest of US protected areas (Buxton et al 2017a), we found high overall median noise exceedance (>10 dB) in one-third of US national park units (2% of all park area). These levels of noise have been shown to affect the body condition (Phillips et al 2018), behavior (Klett-Mingo et al 2016, and fitness (Schroeder et al 2012) of many wildlife species. Ultimately, this level of noise exceedance can affect ecosystem services, altering processes like seed dispersal and pollination (Francis et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Predation pressure has been shown to increase with urbanization (Fischer et al 2012); yet, potential influences of predation on dawn chorus timing remain untested. Additionally, although supplementary feeding is widespread in cities and can alter avian body condition (Amrhein 2014, Phillips et al 2018, Baverstock et al 2019, the effects of feeders on dawn chorus timing remain controversial, so that a larger sample of studies of its impacts would be valuable.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%